The Pattern of Development of Islamic Education (Historical Studies) - Moch Tolchah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
his reseach aimed to determine the pattern of development of islamic education. The method used in this reseach was qualitative. The results of this research, the period before Indonesia's independence there are different patterns of development of Islamic education, namely: (1) isolatif-traditional, in the sense of not willing to accept anything that smells Western (colonial) and the inhibition effect of modern thinking in Islam to enter into it, as was evident at the boarding school education featuring only traditional religious sciences of Islam and common knowledge is not at all given. The essence of Islamic education is an effort to conserve and maintain the treasures of earlier scholars thought as expressed in their books. The main purpose of education is to prepare prospective chaplain or clergy only controlled religious issues alone. (2)Synthesis, which brings the livery (Islamic boarding school) and the new style (colonial or Western education model) tangible schools or Madrasah. In reality, patterns of thought this synthesis contain some variation of the pattern of development of Islamic education. (3) Various models and patterns of development of Islamic education are essentially intends to develop teachings and fundamental values contained in the Quran and al-Sunnah. It's just that they have a different perspective to understand and describe the nature of Islamic education and science. This implies also to formulas educational objectives, content / Islamic education materials as well as aspects of the methodology. Key Words: Islamic Education, Madrasah, Boarding School, Modern School